If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + 1) = 5x + 25 Reorder the terms: 10(1 + x) = 5x + 25 (1 * 10 + x * 10) = 5x + 25 (10 + 10x) = 5x + 25 Reorder the terms: 10 + 10x = 25 + 5x Solving 10 + 10x = 25 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10 + 10x + -5x = 25 + 5x + -5x Combine like terms: 10x + -5x = 5x 10 + 5x = 25 + 5x + -5x Combine like terms: 5x + -5x = 0 10 + 5x = 25 + 0 10 + 5x = 25 Add '-10' to each side of the equation. 10 + -10 + 5x = 25 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 25 + -10 5x = 25 + -10 Combine like terms: 25 + -10 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 2(w+l)=2w+2l | | 3(x+20)=15 | | x/6-x/7=3/7 | | (a-16)/5=29 | | a-16/5=29 | | a-16/5=-8 | | 12x-18=10x | | 7(v-4)=14 | | (a-16)/5=-8 | | -6u+3=-3(u-3) | | 6sen(A)-3=0 | | -3m=-4+8 | | a^2+11a+10=0 | | (6d+5)(d-8)= | | X/5=12/35 | | 28x^2-94x+60=0 | | 28x^2-94x+30=0 | | (3c^2+2c-1)(2c^2+c+9)= | | xy-2a-2x+ay= | | 3x^2+9x-1= | | (3c+2c-1)(2c^2+c+9)= | | 3a^2+6a+2=0 | | 3u^3+15u^2-87u-315=0 | | -10.8/-2= | | 4+3(3a+3)=5 | | 0.01x-1.5=0.009 | | 3.14*R^2*12=258.75 | | pi*r^2*12=258.75 | | 1/10x-1/15=-1/6 | | 4/38x27/8 | | 7/9*n=7/10 | | -10.8/(-2)= |